Literature Review: Keberadaan Mikroplasik Pada Sumber Makanan Beserta Dampaknya Terhadap Kesehatan - Ni Made Seni Antari (Universitas Ivet, 2025)
Microplastic pollution has been widely reported in aquatic environments, including in water, sediment, and organisms like fish. The presence of microplastics in aquatic ecosystems is a significant environmental concern due to the potential harm they can cause to aquatic life. This study aims to determine the presence of microplastics in food sources and their health impacts. The research was conducted as a literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) method. Articles were selected based on inclusion and exclusion criteria from Google Scholar, PubMed, and ScienceDirect. The results show that microplastics are present in food sources such as fish, tofu, and water. Microplastics were also found in human feces. The harmful effects of microplastic contamination on humans, including through organisms like fish, can lead to their accumulation in the respiratory tract, digestive tract, and other organs, causing irritation. If left for a long time, this can lead to inflammation, which may trigger the development of tumors or even cancer. This study concludes that microplastics are present in food sources and can have adverse health effects.